MODEL PENGENDALIAN NYAMUK ANOPHELES ACONITUS DENGAN ASAP â€œLAMPU TEMPLEKâ€ DARI MALATHIONE YANG DIBANDINGKAN DENGAN ALFA-CYPERMETRINE - Abrory, Imam; Boesri, Hasan (Lembaga Penelitian Universitas YARSI, 2007)
Malaria, one of vector borne disease has been still a major Public Health problem in Indonesia. The disease is spread by Anopheles biting, for example Anopheles aconitus. So far, efforts which have been conducted by the government to control the disease is house spraying program with thermal fogging and also Ultra Low Volume (ULV) with Malathione 96 EC. A commercially available insecticide Fendona 30 EC is commonly used equal to Malathione 96 EC in its application. The application of insecticides through ?Templek lamp? would be predicted more applicable due to its simple use by the community. The purpose of this study was to learn the efficacy of trial using ?Templek lamp? of Malathione 96 EC and Fendona 30 EC to find the Lethal Concentration 90% (LC90), Lethal Time 50% (LT50) and 90% (LT90) of insecticides to Anopheles aconitus mortality. An experimental research with posttest only control group design was used in this study. Female An. aconitus, age 2-5 days were purposely selected. They were fed with 10% sugar and tested by Glass chamber method with double control groups. Groups of 20 An. aconitus each were tested with various concentrations of the insecticides, i.e. 0.1%, 0.5%, 1.0%, 2.5% and 5.0% in triplicate. The result showed that based on probit analysis, Fendona 30 EC LT50s at the aforementioned concentrations were 7.25, 5.81, 3.48, 1.16 and 0.54 hours respectively. On the other hand Malathione 96 EC LT50s at the same concentrations were 8.13, 5.48, 3.96, 2.69 and 0.57 hours. At the same concentrations, Fendona 30 EC LT90s were 61.76, 54.96, 20.56, 5.95 and 1.44 hours respectively, while Malathione 96 EC LT90s were 86.37, 43.62, 26.60, 18.86 and 1.48 hours respectively. It was also observed that LC90 for Fendona 30 EC and Malathione 96 EC was 0.688% and 1.048% respectively. Analysis of variance showed significant difference (p 0.05) between concentrations of each insecticides. Further studies are still required to confirm this observation.